Ag@Au nanoprism-metal organic framework-based paper for extending the glucose sensing range in human serum and urine. Issue 21 (17th May 2017) - Huang, Pin-Hsuan; Hong, Chia Ping; Zhu, Jian Fan; Chen, Tzu-Ting; Chan, Chu-Ting; Ko, Yu-Chien; Lin, Tien-Li; Pan, Zheng-Bang; Sun, Ning-Kuei; Wang, Ying-Chu; Luo, Jong-Jheng; Lin, Tzu-Chieh; et al.
Abstract : Ag@Au nanoprism-MOFs-based paper for enhancing the glucose sensing range in human serum and in urine. Abstract : In this work, we present a Ag@Au nanoprism-metal–organic framework-paper based glucose sensor for rapid, sensitive, single-use and quantitative glucose determination in human serum. To achieve painless measurement of glucose with a non-invasive detection methodology, this biosensor was further tested in human urine. In this approach, a new hybrid-Ag@Au nanoprism loaded in close proximity to micrometer sized coordination polymers as phosphorescent luminophores significantly enhanced the emission intensity due to metal-enhanced phosphorescence and worked as reaction sites to support more dissolved oxygen. Reports of enhanced phosphorescence intensity are relatively rare, especially at room temperature. The true enhancement factor of Ag@Au-phosphorescent metal–organic frameworks on paper was deduced to be 110-fold, making it a better optical type glucose meter. The results demonstrate the validity of the intensity enhancement effect of the excitation of the overlap of the emission band of a luminophore with the surface plasmon resonance band of Ag@Au nanoprisms. Ag@Au nanoprisms were used not only to improve the detection limit of glucose sensing but also to extend the glucose sensing range by enhancing the oxygen oxidation efficiency. The oxidation of glucose as glucose oxidase is accompanied by oxygen consumption, which increases the intensity of the phosphorescence emission. The turn-on type paper-based biosensor exhibits a rapid response (0.5 s), a low detection limit (0.038 mM), and a wide linear range (30 mM to 0.05 mM), as well as good anti-interference, long-term longevity and reproducibility. Finally, the biosensor was successfully applied to the determination of glucose in human serum and urine.